Current and prospective development trends of farmland resource conservation in coastal cities: a case study of Jiangsu, China - Li, Yuting; Zhuang, Shu; Li, Yujie; Xu, Yixin; Wang, Nana; Feng, Yongxiang (Frontiers in Sustainable Food Systems, 2025)
The rapid economic development of coastal cities has significantly constrained the availability of farmland resource. Therefore, understanding land-use change dynamics over the past two decades in these regions is essential for promoting the sustainable management of farmland. In this study, based on historical land-use data from the coastal cities of Jiangsu Province, we analyzed the spatiotemporal patterns of land-use change from 2000 to 2020 using remote sensing image interpretation with ArcGIS, construction of land-use change transition matrices, and calculation of land-use dynamic indices. Furthermore, we integrated the PLUS model with a Markov chain approach to simulate potential land-use patterns in 2035 under three future scenarios: natural development, ecological protection, and farmland protection. The results showed that paddy occupied the largest proportion of land use in the study area, ranging from 43.1 to 39.5%, followed by upland, which accounted for 37.7 to 36.5%. Both paddy and upland exhibited continuous declines during the study period, with total reductions of 1,086.67 km2 and 381.35 km2, respectively. The loss of farmland was primarily driven by conversion into built-up land, which expanded by 1,003.61 km2. Transition matrix analysis further revealed that between 2005 and 2010, built-up land experienced a net increase of 1,154.93 km2, of which 55.4 and 34.0% were converted from paddy and upland, respectively. Additionally, statistical analysis identified GDP, population density, annual precipitation, and annual average temperature as the main driving factors influencing land-use change. Simulation results indicated that under both the natural development and ecological protection scenarios, upland would experience slight increases of 32.8 km2 and 10.5 km2, respectively, by 2035. However, paddy would decrease significantly by 466.9 km2 and 476.8 km2 under these two scenarios. In contrast, under the farmland protection scenario, both paddy and upland would increase by 22.6 km2 and 63.1 km2, respectively, by 2035. In conclusion, under the current trajectory of land-use change, the consistent enforcement of farmland protection policies, together with targeted measures for paddy conservation, is crucial for achieving the sustainable utilization of farmland resource in the coastal cities of Jiangsu Province.